Relationship between Energy Consumption and Real Gross Domestic Production in Turkey: A Co-integration Analysis with Structural Breaks - Umit, A. Oznur; Bulut, Elif (International Journal of Energy Economics and Policy, 2015)
Energy is one of the most fundamental requirements for a sustainable economy in many of the emerging countries. Being one of these emerging countries, Turkey has inadequate energy sources and this increases its foreign source dependency for energy. Likewise, experiencing negative energy shocks decreases the economic growth rate. Analyzing the relationship between energy consumption and economic growth by taking into account the structural changes caused by internal shocks and external shocks experienced in the country is of great importance for the Turkish economy. In this study, the long term relationship between energy consumption and real gross domestic production in the period between 1960 and 2012 has been investigated by employing co-integration methods and the vector error correction model. Results of our study show that there is a long term relationship between the series and one-way causality from real gross domestic production to energy consumption. These findings clearly state that economic growth has an important role in energy consumption. Keywords: Energy Consumption; Economic Growth; Co-integration Test with Multiple Structural Breaks JEL Classification: C32; O4; Q43